2018
DOI: 10.3892/ol.2018.8818
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of microRNA profiling in sphere‑cultured ovarian carcinoma cells

Abstract: Abstract.Ovarian cancer is an aggressive and lethal cancer, which in part, can be attributed to complications in the effective detection of this disease during early stages of progression. Frequently, epithelial ovarian cancer is disseminated to the abdominal cavity and forms multicellular aggregates. This unique early metastatic event, and formation of the multicellular aggregate is implicated to provide a basis for understanding the underlying molecular mechanisms of metastasis in ovarian cancer. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We observed an increased number of differentially expressed miRNAs in spheroid conditions than adherent conditions by miR-seq and noted similarities in the differential miRNA expression in our study with miRNAs expressed in other ovarian cancer models. The differential miRNA expression of two-dimensional adherent or three-dimensional spheroid culture conditions in an SKOV3-ipl model were previously reported [21]; their study identified 71 up-regulated and 63 down-regulated miRNAs. In that study, hsa-miR-34a-5p was up-regulated in 3D-sphere-cultured SKOV3-ipl cell lines, and we observed its upregulation in OV90 spheres.…”
Section: Discussionmentioning
confidence: 79%
“…We observed an increased number of differentially expressed miRNAs in spheroid conditions than adherent conditions by miR-seq and noted similarities in the differential miRNA expression in our study with miRNAs expressed in other ovarian cancer models. The differential miRNA expression of two-dimensional adherent or three-dimensional spheroid culture conditions in an SKOV3-ipl model were previously reported [21]; their study identified 71 up-regulated and 63 down-regulated miRNAs. In that study, hsa-miR-34a-5p was up-regulated in 3D-sphere-cultured SKOV3-ipl cell lines, and we observed its upregulation in OV90 spheres.…”
Section: Discussionmentioning
confidence: 79%
“…An earlier bioinformatic analysis of miRNAs expression of FGCs showed that 139 associated pathways were screened out during the growth and selection of dominant follicles [ 69 ]. Furthermore, Cha et al 83 reported that 48 signal transduction pathways are up-regulated by miRNAs and 29 pathways are down-regulated by the miRNAs [ 80 ]. Nowdays, it has been clearly undetermined how many signal transduction pathways are involved in the miRNAs regulation roles [ 8 , 64 ].…”
Section: Molecular Signaling Pathways Were Summarizedmentioning
confidence: 99%